Trends in Scientific Production on Greenwashing based on Scopus (1990-2023) - Gallo Aguila, Carlos Ignacio; Castro Arellano , María del Pilar; Rodríguez Vega, Marco Antonio; Barturen Mondragón, Eliana Maritza; Quezada Castro, María del Pilar; Quezada Castro, Guillermo Alexander (International Journal of Energy Economics and Policy, 2024)
Greenwashing is a misleading practice that affects environmental sustainability and has an impact on the organizational, social, and environmental levels, as it is generated to create a non-real and illusory image of ecological responsibility. The present study conducted a review of the scientific production in the Scopus database, obtaining 1438 documents. Inclusion criteria were used and the PRISMA statement was used to guide the documentary analysis. Likewise, bibliometric tools such as VOSviewer and Biblioshiny were used. The results obtained show that the topic of study has grown exponentially in recent years and the keywords that stand out are corporate social responsibility, environmental communications and reporting, normative regulation, and implications at the financial, social, and ethical levels. There is also interest in consolidating new collaborative networks among authors, with the most cited paper being "The drivers of Greenwashing". It was concluded that greenwashing is a multidisciplinary phenomenon that requires attention from the scientific community and that it is the clients or consumers who perceive the lack of ethics and the absence of environmental commitment in organizations. Criminal liability arising from greenwashing is identified as a future line of research.